Risk Identification and Evaluation of Customs Management Based on Fuzzy Neural Network Algorithm - Duan, Jing Hui (Applied Mechanics and Materials, 2013)
By using fuzzy-neural network algorithm, this paper empirically studied the customs management risk in China. Our research process is summarized as follows: firstly, we describe the situation and development trends of customs management risk; secondly, we employ fuzzy artificial neural network algorithm to establish a conversion mechanism model; finally, we test the effect of this model according to related customs risk management information.